Transactional Drafting Introduction to Contract Drafting and Transactional Practice - Fernandez, Ben L. (Open textbook library., 2021)
Transactional Drafting: Introduction to Contract Drafting and Transactional Practice contains a condensed presentation of all of the topics typically covered in an upper-level law school class on contract drafting. The book covers drafting from scratch including writing in plain English (not using legalese), avoiding ambiguity, and drafting covenants, rights and prohibitions consistently (using "will" or "shall" for covenants, "may" for rights, and "will not" or "shall not" for prohibitions). And it covers contract organization, from the title and the exordium to the core covenant, deal provisions and "boilerplate," to the testimonium and the signature blocks. The book also includes material on getting up to speed before you start drafting and brainstorming for contingencies after you have finished. In addition to drafting from scratch the book introduces students to the wide range of skills involved in transactional practice. There are chapters on revising form documents, both when you are the original drafter and when you represent the other side. Also, the book includes chapters on negotiating contract language, handling a closing (i.e., verifying authority and getting the documents signed), dealing with ethical issues that arise in contract drafting and execution, drafting a contract amendment, and using computers to draft contracts. Transactional Drafting includes everything students need to know to “hit the ground running” as a transactional attorney.